The Eastern coast of the Red Sea in Geographical Sources and the Moroccan and Andalusian Voyages in between the two Centuries (4-6 AH / 10-12 AD) Using Geographic Information Systems - Al-Harbi, Mona Salem; Al-Rehily, Wafa Zabin (Journal of Humanities & Social Sciences, 2023)
The Red Sea is one of the main routes taken by travelers, pilgrims and merchants during their travels to the Arabian Peninsula since ancient times, and accordingly, marinas and stations appeared on its eastern coast that had a role in the continuity of voyages and linking the Arabian Peninsula with other countries. This study sought to shed light on the eastern Red Sea coast through geographical sources and the Moroccan and Andalusian voyages that were composed between the fourth to the sixth centuries AH / tenth to twelfth century AD, using Geographic Information Systems (GIS) through tracking the most important sites associated with this coast and identifying them astronomically and geographically, the most important of which are the marinas that appeared on this eastern coast as a result of natural factors that contributed to its creation. A number of spatial analyzes were applied with geographic information systems, including the pattern of geographical distribution of the marinas of the eastern coast of the Red Sea during the study period, as a new scientific addition to the geography and history of the eastern coast of the Red Sea. The study found that the distribution pattern of ports in the study area adopts a divergent distribution pattern.